SURVEY PERILAKU PEMILIH PILKADA BANJAR 2008 - Edi Kusmayadi; Akhmad Satori; Mohammad Ali Andrias; Subhan Agung; Taufik Nurohman; Wiwi Widiastuti (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
Competition of election mayor of banjar city very tight and the results is no easy to guess. There are too many variable who affected of the candidates victory, which is, political party sponsored, solid campaign team, big budget, campaign central messages, campaign method, candidate imageand constituent treatment can become an significant variable to get the victory. Scientific method who accurate and trusted to understood the voters with make a survey. Survey can show strength and weakness the candidates infront of the voters..Specifically, the information who get from survey are, first popularization measure, second, election level possibility, third, votes reason mapping, forth, significant issued identification, Fifth, campaign strategy identification. Concerned with that, behavior voters survey would become considerable value political mapping for the candidate to get a victory.Research result indicate people animo about election mayor of banjar city are very huge. People aspiration include individual characteristic figure, which is, integrity, economic capability, drummed up region commitment, leadership provisionally put a finger on abig attention accordingly the heftiest candidate mayor of banjar city hold on incumbent mayor dr. Herman Sutrisno.